Impact of Sustainability Reporting on Financial Performance: Evidence from an Emerging Economy - Sohag Ahmed Sunny; Fatema Ali Apsara (Journal of Risk Analysis and Crisis Response (JRACR))
This study investigates the relationship between sustainability reporting and financial performance in Bangladesh's textile industry, focusing on economic, social, and environmental dimensions. Using a sample of 270 firm-year observations, the study employs pooled OLS regression to analyze the impact of sustainability reporting on return on assets (ROA) and earnings per share (EPS). The findings reveal that economic and environmental sustainability reporting have significant positive relationships with both financial performance measures, while social sustainability reporting shows no significant impact. Environmental reporting emerges as the strongest predictor of financial performance, suggesting that environmental initiatives create value through multiple channels, including operational efficiency and market recognition. The study contributes to the literature by providing the first empirical evidence from Bangladesh's textile industry, offering insights for policymakers and corporate leaders in emerging economies. While the findings support stakeholder and legitimacy theories, the study's limitations include its focus on a single industry and reliance on secondary data. The research implications suggest that firms should prioritize environmental and economic sustainability reporting while developing more effective approaches to social sustainability practices that can demonstrate clear financial benefits.